Psychiatric morbidity of patients with keratoconus: A cross-sectional study - TOKER, AYŞE EBRU; YARGI, BERRU; YILDIZ, MESUT; ERGÜN, SERHAT (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Background: This study aimed to determine the prevalence of psychiatric disorders in patients with keratoconus and the effect of clinical parameters and psychiatric morbidity on quality of life in this patient group. Materials and methods: This cross-sectional study enrolled 94 patients with keratoconus. All patients underwent a complete ophthalmic and psychiatric examination and completed the The National Eye Institute Refractive Error Quality of Life Instrument-42 (NEI-RQL-42), Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI) questionnaires. The current diagnosis of psychiatric disorders was determined using the Structured Clinical Interview for DSM-IV (SCID). The impact of disease severity (binocular BCVA >0.4 logMAR, steep K reading >52, and Amsler-Krumeich grades) on vision-related quality of life was also analyzed. Results: The patients? mean age was 23.9 ? 4.8 (range, 18?40) years. Of the 94 participants 35 (37.2%) had a psychiatric diagnosis, 13 (13.8%) had moderate-severe depression and 20 (21.2%) had moderate-severe anxiety according to the BDI and BAI, respectively. The probability of having a psychiatric disorder was higher if the keratoconus was more severe. Patients with a psychiatric diagnosis scored lower on physical functioning, role limitations due to emotional problems, energy/fatigue; emotional well-being, social functioning and pain subscales of the Short Form-36 (SF-36). Having a SCID-1 psychiatric diagnosis and the presence of a psychiatric disorder did not significantly affect NEI-RQL-42 questionnaire scores. Conclusions: There was high psychiatric morbidity among patients with keratoconus. Having a psychiatric disorder was associated with lower QoL as measured using the SF-36.
Keywords: Cross-sectional study; Keratoconus; Psychiatric morbidity